(untitled) (Archive of Conferences, 2021)
Periphrases, on the other hand, are considered euphemisms and are based on the description of events in such a way as to embody them in the human eye. It is known that from ancient times people not only gave information about things, but also tried to describe, compare and describe their important features, and as a result, the visual means of language were formed. Uzbek is one of the richest languages in speech. One such tool is periphrasis. Although periphrases have been the subject of separate scientific research in both Uzbek and Turkic linguistics, the linguistic features of this phenomenon are waiting to be fully resolved.